Passive remediation for metal-rich mine water using steel slag - Md Zahar, Mohd Syakirin (2017)
Acid mine drainage (AMD) is one of the major environmental pollution that needs to be treated for sustainable environment in the future. AMD formation in the environment has become a great public concern globally due to their effects to human health, flora and fauna. Various efforts have been taken to reduce the metal contamination in AMD through controlling or remediation process. However, the usual conventional method based to treat the AMD problem are costly and required extra procedure to further remove the metal ion from water bodies. This study highlights the potential of steel slag which is industrial by product to remove metal ions from metal-rich acid mine drainage (AMD) based on batch and column system. The removal efficiency, adsorption capacity and behaviors of adsorbents were examined during the metal removal process and incorporated with isotherm and kinetic models. In the batch studies, the removal of metal ions was evaluated by varying the contact time, solution pH, initial metal concentration, adsorbent dosage, size and the effect of competing ions. While for the column study, the factors of adsorbent bed height, flow rate and competing ions were evaluated to obtain the removal performance of steel slag in continuous flow system. Results of batch experiment have indicated >90% metal removal efficiencies when pH of the AMD has reached near-neutral state (6.8- 7.5) at 14 hours contact time. Optimum equilibrium time was found at 24 hours whereby all the metals were 99-100% removed. An increased adsorption capacity with a decreased removal efficiency was observed as initial metal concentration increased. In contrast, increasing adsorbent dosage leads to increased removal efficiency but removal tends to be constant after reaching equilibrium amount of 2.0 g. Comparing the effect of competing ions, Fe was not affected despite the presence of other metal ions (100% removal) compared to Mn (59.3% removal) in mixed AMD solution. The adsorption behavior of Fe, Cu, Zn and Mn fits appropriately with the Langmuir isotherm model compared to Freundlich isotherm model indicated that the adsorption process occurred in monolayer surface rather than heterogeneous surface. The adsorption kinetics followed the pseudo-second-order kinetics trend which is consistent with chemisorption and is supported by the intra particle diffusion process. In the column study, the metal ions uptake mechanism is particularly bed depth and flow rate dependent, favoring higher bed depth at 3 cm and lower flow rate at 10 mL/min. The breakthrough curve simulation for metal ions removal were described using BDST and Thomas model. Both models were applied onto fixed bed column experimental data at different bed depths of 1.5, 2 and 3 cm with a constant flow rate of 10 mL/min and influent metal concentration of 27 mg/L. The linear plots at different bed depths indicate that adsorption of all metal fits well with BDST model. The performance of adsorption capacity for Mn is highly affected in mixed solution, by which 81.1% reduction from value in single solution, while Cu was only slightly affected, i.e. 10.1% reduction from value in single solution. Therefore, this study has highlighted the potential of steel slag as an adsorbent for metal-rich AMD with regard to metal removal efficiency, affecting variables, kinetics and models that explain the metal removal behavior.